Finance Minister Mariano Navarro Rubio's support for Fernando María Castiella's pro-European policy after the implementation of the 1959 Stabilization Plan (Revista de Estudios Europeos, 2024)
This paper offers a brief account of the support given by the promoters of the 1959 Stabilization Plan to the pro-European policy led by Fernando María Castiella. Specifically, it focuses on the role of the Minister of Finance Mariano Navarro Rubio (1957-1965), and it is based on the consultation of his personal archive and other complementary documentary collections.
Keywords: Stabilization Plan; Common Market; EFTA; Navarro Rubio; francoism